Archaeological rescue excavations on packages 3 and 4 of the Batinah Expressway, Sultanate of Oman - Saunders, Ben (British Foundation for the Study of Arabia monographs., 2016)
This report presents the results of rescue excavations conducted during the spring and summer of 2014 in preparation for the construction of the Batinah Expressway (packages 3 and 4) on the Batinah coastal plain in al-Batinah North Governate.